Answer:
$638641.33
Step-by-step explanation:
Adam earns $45,000 in his first year.
His salary increases by 3% each successive year. Therefore, his salary the next year is 103% of his previous year.
This is a geometric sequence where the:
(a)
Sum of geometric series[tex]=\dfrac{a(r^n-1)}{r-1}[/tex]
Substituting the given values, Adam's total earnings over n years
[tex]=\dfrac{45000(1.03^n-1)}{1.03-1}\\\\$Adam's Total Earnings=\dfrac{45000(1.03^n-1)}{0,03}[/tex]
(b)When n=12 years
[tex]\text{Adam's Total Earnings for the first 12 years=}\dfrac{45000(1.03^{12}-1)}{0.03}\\=\$638641.33$ (correct to the nearest cent)[/tex]